Čileanski pisci hrvatskoga podrijetla dominiraju španjolskom Croaticom - Ljubetić, Jerko (2008)
On the list of the most widespread languages Spanish is second, right behind English, with almost 400 million speakers among which are over a half million of our emigrants. Since Croatians have lived in countries of the Spanish speaking area in significant numbers almost half a millennium, as far back as the time of the Republic of Dubrovnik (1272 – 1808) and have a developed publishing activity for over a century in these regions, the interest of the Croatian Heritage Foundation for Spanish Croatica is logical. The significant cultural imprint, often of high aesthetic achievement, of Spanish Croatica can be found in the countries of Latin America such as Argentina, Bolivia, Chile, Paraguay, Peru and Uruguay, but also in Venezuela and the countries of the European Union. The phenomenon of Chileao-Croatian writers, however, attracts the greatest interest of the expert public. It is known that about two hundred writers of Croatian origin have published in Chile for almost a century (as a rule only in the Spanish language), most hailing from central Dalmatia and its islands, especially Brač. The topics dealt with by Chilean writers of Croatian origin are diverse and follow the trends of Chilean literature, but also introduce innovations into it. Having in mind the high artistic achievements of some of the literary works of Chileao-Croatian writers, the expert public feels that the phenomenon of Chileao-Croatian writers deserves our constant attention and theoretical treatment and to be given its historical place in both Chilean and Croatian literature.
Bibliografske bilješke uz tekst
Summary ; resumen
Keywords: Hrvati -- Književnici; Čile